Economical Feasibility Study of SAGARA UPALA Hotel Construction in Pangandaran - Rasyid, Adhytia Azhari; Aliludin, Arson (Journal of Business and Management, 2015)
Abstract- Any investations are hopefully make a positive return in long term or mid term, but it is always have risk when you spend a money for investation.This research aimed to find the investment feasibility of the company projectÂ so the company can make the correct decision for the investment plan. To solve the problem this research calculate the value of Net Present Value (NPV), investment Interest Rate of Return (IRR), the Investment Payback Period (PBP) of the project The object of this research is a hotel construction in Pangandaran beach, Jawa Barat, Indonesia by PT Graha Mitra Properti. The project will stated as feasible if the Net Present Value (NPV) is higher than 0 (NPV>0) and the Interest Rate of Return (IRR) is higher than the rate of return. The lifetime of this project is 30 years. This research will only explain economical feasibility study based on investment, cash inflow and cash outflow and there are several assumption in this research to limit the the scope of the final project.Â Keywords: B2B marketing, e-commerce, technology acceptance model (TAM), consumer behavior, building materialÂ